Giant Ileocecal Inflammatory Fibroid Polyp: Unique Clinical Presentation. (21st July 2020) - Almaghrabi, Hatim; Almaghrabi, Murouj; Al-Maghrabi, Haneen
Abstract : Inflammatory fibroid polyps (IFPs) are infrequent gastrointestinal tract benign neoplasms. They mostly occur in the stomach especially the antrum. Signs and symptoms depend on their anatomic location and lesion size. Lesion biopsies are very challenging for accurate diagnosis in these lesions. Histopathological examination of resected tissue along with immunohistochemical studies is the perfect way to confirm the final diagnosis. In this paper, the authors present an unusual case of IFP in a 23-year-old female patient presented to the emergency room (ER) with a picture of intestinal obstruction and severe abdominal pain. Her investigations revealed a huge mass located at the ileocecal valve, with overall features mimic gastrointestinal stromal tumor (GIST) clinical presentation. Surgical resection is considered the most commonly used treatment method. The overall prognosis is good with a low risk of recurrence.